Great flying stories / Man´s conquest of the air from the biplane to the ramjet. - Anderson, Frank W. (Dell, 1958)
Introduction - Turnabout - More about the war birds - Air circus - Flying blin - Trapped - New York to Paris - The elements - The greates man in the world - Refueling in the air - Anti-submarine attack - Methods and routes of escape - Max Guedj - The invaders - Peacetime interlude - Leipzig - Majort Blatt - "...recommend inmediate ditching" - The needle - Korea - The jet that crashed before take-off .